Larval therapy from antiquity to the present day: mechanisms of action, clinical applications and future potential. Issue 980 (5th June 2007) - Whitaker, Iain S; Twine, Christopher; Whitaker, Michael J; Welck, Mathew; Brown, Charles S; Shandall, Ahmed
Abstract : When modern medicine fails, it is often useful to draw ideas from ancient treatments. The therapeutic use of fly larvae to debride necrotic tissue, also known as larval therapy, maggot debridement therapy or biosurgery, dates back to the beginnings of civilisation. Despite repeatedly falling out of favour largely because of patient intolerance to the treatment, the practice of larval therapy is increasing around the world because of its efficacy, safety and simplicity. Clinical indications for larval treatment are varied, but, in particular, are wounds infected with multidrug-resistant bacteria and the presence of significant co-morbidities precluding surgical intervention. The flies most often used in larval therapy are the facultative calliphorids, with the greenbottle blowfly ( Lucilia sericata ) being the most widely used species. This review summarises the fascinating and turbulent history of larval therapy from its origin to the present day, including mechanisms of action and evidence for its clinical applications. It also explores future research directions.